Training gut and body: physical activity, diet, ASA and microbiota influence the outcome in gastrointestinal cancer survivors - Oneda, Ester; Noventa, Silvia; Libertini, Michela; Cherri, Sara; Manno, Alessandra; Meriggi, Fausto; Martinetti, Michele; Zaniboni, Alberto (Frontiers in Nutrition, 2025)
Gastrointestinal (GI) cancers remain a significant contributor to global cancer mortality. Recent evidence highlights the crucial role of lifestyle interventions—particularly physical activity and diet—in improving outcomes for GI cancer survivors. This comprehensive review explores how structured exercise, in combination with dietary strategies and selective pharmacologic interventions like aspirin, can modulate key biological processes including insulin sensitivity, inflammation, immune response, and gut microbiota composition. A central theme is the modulation of the gut microbiota. Physical activity and diet promote microbial diversity and the growth of species with anti-inflammatory and immunostimulatory properties—effects that may enhance therapeutic efficacy and resilience to treatment toxicity. The concept of a “trained microbiota,” inspired by studies in athletes, is proposed as a model to understand how lifestyle can durably shape host–microbe interactions. Furthermore, aspirin use in genetically selected populations shows promise in reducing recurrence, highlighting the potential for integrated, low-risk interventions. Finally, exercise improves quality of life, functional capacity, and treatment tolerance, while reducing fatigue and psychological distress. Translating these findings into practice requires structured integration into oncology care pathways, with multidisciplinary collaboration and tailored prescriptions of physical activity—combining aerobic and resistance training, nutritional support, and psychological care. Despite the need for further high-quality trials, especially in gastric and pancreatic cancer, current data provide a strong rationale for promoting lifestyle-based strategies as adjunctive therapy in gastrointestinal oncology. The review advocates for a paradigm shift in survivorship plans—one that integrates physical training, nutritional optimization, and microbiota support to enhance long-term outcomes in GI cancer survivors.